#### Answer

73

#### Work Step by Step

$2y^2-4y+3$ $\longrightarrow$ substitute given values
$=2(-5)^2-4(-5)+3$ $\longrightarrow$ resolve exponent; multiply
=$2(25)-(-20)+3$ $\longrightarrow$ multiply
=$50+20+3$ $\longrightarrow$ solve
=$73$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

73

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.